The first migrants to Madagascar and their introduction of plants : linguistic and ethnological evidence - (:unkn) unknown (My University, 2011)
The Austronesians who settled in Madagascar in the first millennium of the Christian Era were probably different from the Austronesians who reached the East African coast earlier at different times, bringing bananas, taro and yam (Blench 2010). Based on linguistic data, this article proposes that four plants were brought by the first Austronesians in Madagascar: rice, water yam, coconut and Indian saffron. These plants helped the Austronesians to begin the process of colonizing well-watered areas, cultivated both through wet and swidden agriculture. A little later, populations coming from the East African coast introduced other plants (sorghum, cowpea, Bambara pea, banana...) that allowed them to occupy other ecosystems. At the end of the first millennium, different parts of the island were thus already inhabited, on the coasts and in the Highlands, and cultural blendings were already underway. The continuation of migrations, from South-East Asia, from the East African coast and from India in the 2nd millennium would bring increasing complexity in the cultural blendings and allow the repeated introduction of many cultivated plants.
Keywords: African Research